CHANGES IN INVESTMENT PATTERNS IN INDONESIA DURING THE COVID-19 (Case Study of Foreign Investment in the Health and Social Work Sector) - Amrizal Amrizal; Adi Putra; Mukhlis Mukhlis (International Journal of Economics, Business and Innovation Research, 2023)
The negative effects of the Covid-19 pandemic have been felt by international trade players in Indonesia. The coronavirus outbreak that spread at the end of 2019 has hit economic activities including foreign investment in the health and social work sector in Indonesia. Decreased investment will lead to reduced employment and encourage increased unemployment in Indonesia. The purpose of this study is to determine whether there are differences in exchange rates and foreign investment in the health sector and social workers before the pandemic with during the covid-19 pandemic in Indonesia. This research method uses quantitative research, using secondary data obtained from BPS and Bank Indonesia publications. The data used is cross-time data, namely 2017-2019 and 2020-2022. The data analysis method uses the Paired Sample Test. The results showed that the value of foreign investment in the health and social work sector had no significant difference between the 3-year period before the Covid-19 pandemic and the 3-year period during the Covid-19 pandemic. The average growth of investment in the pre-pandemic period was 74.42 per cent, which was greater than during the pandemic period, which was 34.75 per cent. The exchange rate of the rupiah against the U$ dollar has a significant difference between the 3-year period before the Covid-19 pandemic and the 3-year period of the Covid-19 pandemic. The average exchange rate of the rupiah during the pre-pandemic period was IDR 13,919, this was lower than during the pandemic which was IDR 14,538.